PENYULUHAN HUKUM PERLINDUNGAN DATA PRIBADI DI SUB DIREKTORAT HUKUM KORPORAT PT PLN (PERSERO) - Rama Dhianty (Abdi Bhara, 2022)
One of the challenges faced by PT PLN(Persero) as a State-Owned Electricity Company, isthe phenomenon of technological disruption. In linewith this, currently PT PLN (Persero) has digitized itsgeneration, transmission and distribution operations,as well as digitized customer service. Digitalization ofcustomer service is carried out by PT PLN (Persero)by launching the New PLN Mobile application onDecember 18, 2020. PLN customers through the NewMobile PLN application can access all services viasmartphones. The launch of New PLN Mobileultimately made PLN an Electronic System Operator.Based on Government Regulation Number 71 of 2019concerning the Implementation of Electronic Systemsand Transactions, PLN as an Electronic SystemOperator has obligations, especially obligationsrelated to the management, processing, storage andguarantee of customer personal data protection. Theactivity called "Knowledge Sharing" at the Sub-Directorate of Corporate Law was held through awebinar legal counseling method with the theme"Personal Data Protection". The participants were136 people. The material presented in this webinar isabout (1) background on the need for personal dataprotection, (2) Which belongs to the category ofpersonal data, (3) Rights and obligations of ElectronicSystem Operators and Users. The results of this legalwebinar are (1) increasing understanding related topersonal data protection, and (2) understanding theobligations of PLN as an Electronic System Operator,especially related to personal data.